Readers’ Perceptions of Lexical Cohesion in Text - Morris, Jane (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Preliminary results from an experimental study of readers’ perceptions of lexical cohesion and lexical semantic relations in text are presented. Readers agree on a common “core” of groups of related words and exhibit individual differences. The majority of relations reported are “non-classical” (not hyponymy, meronymy, synonymy, or antonymy). A group of commonly used relations is presented. These preliminary results indicate potential for improving both relations existing in lexical resources, and methods dependent on lexical cohesion analysis. Les résultatspréliminaires d’une étude expérimentale sur les perceptions des lecteurs au sujet de la cohésion lexicale et des relations lexicales sémantiques de textes sont présentés. Les lecteurs s’entendent sur un « noyau » commun de groupes de mots reliés et présentent des différences individuelles. La majorité des relations indiquées sont « non classiques » (ni hyponymiques, méronymiques, synonymiques ou antonymiques). Un groupe de relations couramment utilisées est présenté. Ces résultats préliminaires indiquent le potentiel nécessaire pour améliorer aussi bien les relations existant dans les ressources lexicales que les méthodes dépendant de l’analyse de la cohésion lexicale.